2015
DOI: 10.1021/ja511349p
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Platinum Nanoparticles with l-Proline: Simultaneous Enhancements of Catalytic Activity and Selectivity

Abstract: In this work we present the successful application of functionalizing Pt nanoparticles (NPs) with hydrophilic organic ligands as a strategy for enhancing their catalytic activity and selectivity. In the first step, Pt NPs were prepared by a colloidal approach and subsequently functionalized in a separate synthesis step with L-proline (PRO). The functionalized NPs were supported onto Al2O3 and investigated as heterogeneous catalysts for the selective hydrogenation of acetophenone. Whereas significant amounts of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
149
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(160 citation statements)
references
References 47 publications
5
149
0
1
Order By: Relevance
“…All samples show good selectivities (defined as the concentration of hexene with respect to the concentration of all reaction products), which ranges from 75 to over [11,[17][18][19][20]44]. However, an acceleration of the reaction by amine ligands, as it has been previously reported for supported platinum nanoparticles protected by L-proline in the hydrogenation of acetophenone [45], is not observed. While particles stabilized by amines or the phosphine react equally fast, protection by thiols lead to a strong decrease in the reaction rate.…”
Section: Catalysissupporting
confidence: 48%
See 1 more Smart Citation
“…All samples show good selectivities (defined as the concentration of hexene with respect to the concentration of all reaction products), which ranges from 75 to over [11,[17][18][19][20]44]. However, an acceleration of the reaction by amine ligands, as it has been previously reported for supported platinum nanoparticles protected by L-proline in the hydrogenation of acetophenone [45], is not observed. While particles stabilized by amines or the phosphine react equally fast, protection by thiols lead to a strong decrease in the reaction rate.…”
Section: Catalysissupporting
confidence: 48%
“…For such cases and for the nanoparticle protection by amines others than quaternary ones, it seems that a binding mode is generally accepted, in which the amine binds via the lone-pair of the nitrogen atom to the particles [23,45,49]. This is in analogy to complex chemistry and other metal nanoparticles, such as gold [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, Kunz and coworkers demonstrated that both the catalytic activity and selectivity were improved simultaneously using the hydrophilic chiral ligand L-proline. 102 The resulting platinum catalyst was highly chemoselective toward the desirable aromatic alcohol with modest stereoselectivity (14% ee) in the hydrogenation reaction of acetophenone ( Figure 13). Heterogeneous asymmetric catalysts with bimetallic NPs have also been successfully developed in recent years.…”
Section: Chiral Ligands and Modifiers For Asymmetric Catalysismentioning
confidence: 99%
“…[9][10][11] However, even for the much simpler spontaneous self-assembly, which has been intensively studied, the underlying basic science is still not fully understood. 12,13 The SAM studied here, is the earliest 1 , and simplest example of an organic SAM.…”
Section: Introductionmentioning
confidence: 99%